(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the formation of feminist ideas in the mass media of Uzbekistan and the transformation of the socio-political perspectives of female journalists. The research explores the historical development of female journalism, covering stages from the Jadidism era to the modern digital media age. Furthermore, the transition of the female image in media from stereotypical depictions to an independent, intellectual subject is examined through sociological and discursive analysis methods, alongside existing barriers in gender equality and media policy. The article concludes by presenting scientific and practical recommendations for enhancing the activism of female journalists and ensuring gender balance in the media sphere.